Inovasi Tas Unik dan Estetik dari Tali Kur sebagai Produk Fashion Ramah Lingkungan dan Bernilai Ekonomi Tinggi - Trie Hierdawati; Definna Rahmadewi; Sindi Dwi Hartina; Siti Maryam; Sulistiana Sulistiana (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2026)
The rapid development of the fashion industry has led to increasing environmental problems due to textile waste and the use of environmentally unfriendly materials. This study aims to analyze the potential innovation of kur rope bags as an environmentally friendly fashion product with high economic value. The research method used is a descriptive qualitative method through observation, literature study, and documentation of the kur rope bag manufacturing process. The results show that kur rope has strong, durable, and flexible characteristics, making it suitable for use as a basic bag material. Innovation in design and weaving techniques can increase the aesthetic value and marketability of the product. In addition, kur rope bags have the potential to become a promising business opportunity and support the empowerment of the community's creative economy. With growing awareness of sustainability, kur rope bags can become an alternative fashion product that not only reduces environmental impact but also creates new market opportunities. Therefore, the development of this product is expected to contribute positively to reducing textile waste and strengthening the local economy through the creative industry.